A Convexity Property of Discrete Random Walks. (31st March 2016) - NAGY, GÁBOR V.; TOTIK, VILMOS
Abstract : We establish a convexity property for the hitting probabilities of discrete random walks in Z^d (discrete harmonic measures). For d = 2 this implies a recent result on the convexity of the density of certain harmonic measures.